Use of thermogravimetric analysis to estimate collagen and hydroxyapatite contents in archaeological bone. (September 2022) - Durga, Ricky; Jimenez, Natalia; Ramanathan, Sivakumar; Suraneni, Prannoy; Pestle, William J.
Abstract: In this study, we evaluate whether thermogravimetric analysis (TGA) can be used to estimate the amounts of collagen and hydroxyapatite in archaeological bone accurately and rapidly, through evaluation of twenty-four previously analyzed archaeological human bone samples. Mass losses in the approximate ranges of 300–500 °C, 220–600 °C, and 600–900 °C, correspond to collagen mass loss, total organic mass loss, and hydroxyapatite mass loss, respectively. The first two mass losses (300–500 °C and 220–600 °C) show strong correlations with independently determined collagen content; however, the correlation between the third loss range (600–900 °C) and hydroxyapatite content was poor. Thus, TGA appears to be a good technique for estimating collagen but not apatite content in archaeological bone. As thermogravimetric analysis requires small amounts of material (tens of mg) and minimal sample preparation, while avoiding the superficiality of other collagen quantification methods (e.g., vibrational spectroscopy), it appears to be a promising technique for further archaeological exploration. Highlights: Thermogravimetric analysis (TGA) reliably estimates bone collagen content. TGA does not provide reliable estimates of bone hydroxyapatite. TGA is a complementary minimally destructive tool for screening archaeological bone.